2018
DOI: 10.1002/chem.201804768
|View full text |Cite
|
Sign up to set email alerts
|

Submerging a Biomimetic Metallo‐Receptor in Water for Molecular Recognition: Micellar Incorporation or Water Solubilization? A Case Study

Abstract: Molecular recognition in water is an important topic, but ac hallenging task due to the very competitive nature of the medium. The focusofthis study is the comparison of two different strategies for the water solubilization of ab iomimetic metallo-receptor based on ap oly(imidazole) resorcinarene core. Thef irst relies on an ew synthetic path for the introduction of hydrophilic substituents on the receptor,a taremote distance from the coordination site. The second involves the incorporation of the organosolubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Some useful starting points for the design of such ligands exist in the field of anion sensing, ,,,, but additional advances are needed, particularly in polar solvents. Cryptand ligands and supramolecular complexes that recognize and bind specific alkali metal cations are known, yet the corresponding chemistry for halides lags far behind. Chromophores that bind specific halide ions and selectively reduce or oxidize them when illuminated with light could be envisioned to enable halide photoredox chemistry in contaminated water or in seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Some useful starting points for the design of such ligands exist in the field of anion sensing, ,,,, but additional advances are needed, particularly in polar solvents. Cryptand ligands and supramolecular complexes that recognize and bind specific alkali metal cations are known, yet the corresponding chemistry for halides lags far behind. Chromophores that bind specific halide ions and selectively reduce or oxidize them when illuminated with light could be envisioned to enable halide photoredox chemistry in contaminated water or in seawater.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the major difficulties encountered for molecular recognition in water originated from a very competitive nature of water medium to the electrostatic interactions and particularly for directional Hbonding. 33,34 We observed that the type of comonomer strongly influenced recognition behavior for a strongly hydrated anionic form of PPA in the rebinding solvent containing ≤50% H 2 O. Hence, MIPs prepared using the hydrophobic comonomer mAA (P2) displayed enhanced binding than those prepared using the hydrophilic comonomer HEMA (P1).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…[8][9][10] A major breakthrough in the development of fully biomimetic systems has been achieved recently with the optimized synthetic procedure for water-soluble structures, which are now readily available. [11][12][13] Permanently positively charged calix [4]arene 2 and calix [6]arene 4 (Scheme 1) studied within this report were among the first examples of our water soluble systems, at the time showing promising recognition of metal cations and primary amines in aqueous solution. 14,15 Previously published calixarene derivatives targeting DNA based their action on the substituents bearing multiple positive charges, which strongly interacted with a DNA negatively charged backbone, in several cases, strongly condensing plasmid-DNA into globular species followed by efficient DNAtransfection into the cells, 5,6 while dimeric derivatives did not cause DNA-condensation but were instead inserted into the DNA major groove.…”
Section: Introductionmentioning
confidence: 81%
“…8–10 A major breakthrough in the development of fully biomimetic systems has been achieved recently with the optimized synthetic procedure for water-soluble structures, which are now readily available. 11–13 Permanently positively charged calix[4]arene 2 and calix[6]arene 4 (Scheme 1) studied within this report were among the first examples of our water soluble systems, at the time showing promising recognition of metal cations and primary amines in aqueous solution. 14,15…”
Section: Introductionmentioning
confidence: 93%